Adições minerais e as disposições normativas relativas à produção de concreto no Brasil: uma abordagem epistêmica - Gustavo Celso da Fonseca (2010)
The use of mineral admixtures as input for civil construction has been increasing at a fast pace in the last decades and most of them derive from steel plants, thermoelectric power plants and industries such as silica fume, fly ash, blast-furnace slags and filler. Historically treated as solid waste, metallurgical slags are now valued in markets worldwide due to their potential for reuse as raw material or as input for other processes. Blast-furnace slag production in Brazil is almost exclusively absorbed by the cement industry. The demands imposed by the Brazilian standards recommended by the ABNT which establishes the criteria for preparation, control and delivery of concrete and defines the parameters of acceptance of cements containing additions are controversial and represent obstacles to the sustainable use of slags. Concrete producers and slag processers in Brazil keep to international standards that acknowledge the use of slags as mineral admixtures directly to concrete, while Brazilian standards allow their use only as a component to be incorporated in the cement manufacturing. Considering the common international practice of adding blast furnace slags directly to concrete as a partial cement replacement, a critical analysis of the Brazilian concrete industry is indispensable from the standpoints of sustainable development and durability of constructions. Such analysis will encompass not only the configuration of the Brazilian cement and concrete industries, but also Brazilian regulations pertaining to the use of mineral admixtures in concrete manufacturing and the consequences of such regulations for the civil construction industry and for society as a whole.